2002
DOI: 10.1080/08958370290084511
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Nerve-Mediated Nasal Vasodilatory Response to Inspired Ethyl Acrylate

Abstract: The irritants acrolein, acetaldehyde, and acetic acid induce a rapid sensory nerve-mediated nasal vasodilatory response in the rat. The aim of the current study was to examine acute nasal sensory nerve-mediated acute responses to an irritant ester vapor, ethyl acrylate. For this purpose, the upper respiratory tract of the urethane-anesthetized male F344 rat was isolated by insertion of an endotracheal cannula, and ethyl acrylate-laden air was drawn continuously through that site at a flow rate of 100 ml/min fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…These exposure concentrations were estimated to approximate the RD 50 based on pilot studies. Our laboratory's previous studies on the rat indicated that local tissue responses were easily demonstrable at RD 50 of each irritant (26,28,29,39).…”
Section: Animals and Chemicalsmentioning
confidence: 99%
See 4 more Smart Citations
“…These exposure concentrations were estimated to approximate the RD 50 based on pilot studies. Our laboratory's previous studies on the rat indicated that local tissue responses were easily demonstrable at RD 50 of each irritant (26,28,29,39).…”
Section: Animals and Chemicalsmentioning
confidence: 99%
“…URT acetone vapor uptake was monitored during exposure as a measure of URT perfusion rates by the methods used in our laboratory's previous studies (26,28,31). Briefly, vapor concentrations in chamber air (C in) and in air that had been drawn through the isolated URT (Cex) were measured by gas chromatography as described above.…”
Section: Animals and Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations